2023
DOI: 10.3389/fpsyt.2023.1122865
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiology of functional neurological disorders characterised by impaired awareness

Abstract: We review the neurobiology of Functional Neurological Disorders (FND), i.e., neurological disorders not explained by currently identifiable histopathological processes, in order to focus on those characterised by impaired awareness (functionally impaired awareness disorders, FIAD), and especially, on the paradigmatic case of Resignation Syndrome (RS). We thus provide an improved more integrated theory of FIAD, able to guide both research priorities and the diagnostic formulation of FIAD. We systematically addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 272 publications
0
1
0
Order By: Relevance
“…Current theories suggest that FND arises from networks in the brain that overlap with anxious and depressive disorder symptomatology and that many FND symptoms are essentially somatization of anxiety or depression‐spectrum pathology. More specifically, current theories postulate that FND is driven by impairments in self‐awareness and predictive coding, which are neurobiologically affected by stress, uncertainty, and neurally encoded beliefs, all of which are highly affected by mood and anxiety disorders (Milano et al., 2023 ). Our findings are similar to other studies of this population, which also demonstrated mean age of onset around 14–15, high rates of anxiety and depression, rapid progression of symptoms, and higher than expected prevalence of FND symptoms (Cavanna et al., 2023a ; Prato et al., 2022 ; Pringsheim et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Current theories suggest that FND arises from networks in the brain that overlap with anxious and depressive disorder symptomatology and that many FND symptoms are essentially somatization of anxiety or depression‐spectrum pathology. More specifically, current theories postulate that FND is driven by impairments in self‐awareness and predictive coding, which are neurobiologically affected by stress, uncertainty, and neurally encoded beliefs, all of which are highly affected by mood and anxiety disorders (Milano et al., 2023 ). Our findings are similar to other studies of this population, which also demonstrated mean age of onset around 14–15, high rates of anxiety and depression, rapid progression of symptoms, and higher than expected prevalence of FND symptoms (Cavanna et al., 2023a ; Prato et al., 2022 ; Pringsheim et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%